Antiinflammatory Activity of The Fruits of Piper longumLinn - Bhitre, M.J.; Fulmali, Sushma; Kataria, Maya; Anwikar, Shraddha; Kadri, Harsha (Asian Journal of Chemistry, 2010)
Inflammation is a response of vascularized living tissue to the local injury. It is the body's defense mechanism, which is closely intertwined with the process of repair. It serves to destroy or dilute the injurious agents and also reconstitute the damaged tissue by regeneration. The severe side effects of steroidal and non-steroidal antiinflammatory drug evoked us to search for new antiinflammatory drugs from the indigenous source. The methanolic, ethanolic, chloroform, ethyl acetate and pet ether extracts of fruits of Piper longum Linn was tested to study the antiinflammatory activity using the technique of carrageenan induced paw edema in albino rats. The extract showed significant antiinflammatory activity comparable to the reference standard aspirin.